HERDING BEHAVIOR IN STOCK INVESTMENT DECISION MAKING - Nyoman Yudha Astriayu Widyari; Putu Ayu Diah Widari Putri; Ida Ayu Komang Tiara Pratistha Sari (LPPM Universitas Bina Bangsa, 2024)
In general, decisions in investing in shares must be made with good consideration, because this concerns the returns and risks that will be obtained. However, in carrying out transactions, investors often behave irrationally, namely by simply following decisions taken by other investors, which is called herding behavior. Investors can herd even though they already have information or personal decisions that they have made, but they ignore this information and personal decisions and prefer to follow the decisions of groups or other people. Herding is one of the actions related to behavioral finance theory, namely the theory of financial decision making seen from a psychological perspective. This theory looks at the extent to which internal emotions will influence the decisions made by investors. In his actions, an investor can also carry out herding actions because they are influenced by market conditions that are occurring at that time. Apart from that, herding itself also has several types of herding that investors can do when making a stock investment decision